Registration of 'Flathead' hard red winter wheat. Issue 3 (31st August 2020) - Berg, J.E.; Stougaard, R.N.; Kephart, K.D.; Chen, C.; Eberly, J.O.; Torrion, J.A.; Lamb, P.F.; Miller, J.H.; Pradhan, G.P.; Ramsfield, R.; Nash, D.L.; Smith, V.; et al.
Abstract: 'Flathead' (Reg. no. CV‐1164, PI 693237) hard red winter (HRW) wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in 2019. Flathead was derived from a composite of two very closely related single crosses of the predominant cultivar 'Yellowstone' to stripe rust resistant source PI 640431, a hard white spring wheat backcross derivative of WA007900 that carries stripe rust all‐stage resistance genes Yr5 and Yr15 . Flathead was developed using a modified bulk breeding method and selected as an F5:6 head row after phenotypic selection for stripe rust resistance at Kalispell, MT. Flathead was tested under the experimental number MT1564 in Montana yield trials from 2015 to 2019. Flathead is a high‐yielding HRW wheat cultivar with early maturity, short stature, medium grain protein concentration, excellent milling and baking quality, and a high level of all‐stage resistance to predominant races of stripe rust. Flathead was released for its early maturity, improved stripe rust resistance, and improved grain yield relative to other Montana‐adapted early heading cultivars.